2022
DOI: 10.21511/im.18(4).2022.12
|View full text |Cite
|
Sign up to set email alerts
|

Marketing research in the context of trust in the public sector: A case of the digital environment

Abstract: Trust in public services is a driving force of socio-economic development. It ensures effective dialogue between citizens and government and becomes especially relevant in the digitalization. The lack of trust in the public sector can make reforms ineffective and the achievement of the goals of the Ministry of Digital Transformation within the framework of the State Strategy for Regional Development of Ukraine until 2027 in question. For this reason, marketing tools in public services should be directed toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…On the other hand, Litovtseva et al (2022) state that their findings underscore the importance of employing marketing tools to cultivate trust in public services and government entities in the digital environment. The exploration accentuates the call for modernization and the formulation of marketing strategies that focus on the correlation between service marketing and consumer behavior.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, Litovtseva et al (2022) state that their findings underscore the importance of employing marketing tools to cultivate trust in public services and government entities in the digital environment. The exploration accentuates the call for modernization and the formulation of marketing strategies that focus on the correlation between service marketing and consumer behavior.…”
Section: Resultsmentioning
confidence: 97%
“…Ultimately, it is concluded that print marketing is indeed a powerful tool for aligning the electorate with the emotional rhythm of information perception. Litovtseva et al (2022) state that the paper presents concepts and suggestions for public sector entities to increase trust through effective digital marketing approaches. The results indicate that public sector marketing is a multidisciplinary field of scientific research that is actively progressing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research design thus combined numerical data to quantify the effects of marketing strategies with descriptive data to capture detailed perceptions and experiences of consumers (Haryadi et al, 2022). The subsequent phase of the research focused on identifying the target population for the survey (Litovtseva et al, 2022). This involved selecting a diverse group of respondents that accurately represented different consumer categories, ensuring a broad range of insights into the impact of online marketing strategies (Prasetyo et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The issue of digitalization in general, the formation of a digital society and the impact of digital technologies on the transformation of approaches to management at various levels are considered by scientists in works [35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Among these studies, it is necessary to single out publications devoted to the problems of security, privacy, data protection and cyber security in smart cities [49][50][51][52][53][54][55][56][57]. These problematic areas are most often used as an argument against the uncontrolled expansion of digital technologies.…”
Section: Authorsmentioning
confidence: 99%